Evidence for an early innate immune response in the motor cortex of ALS - Javier H. Jara; Barış Genç; Macdonell J. Stanford; Peter Pytel; Raymond P. Roos; Sandra Weintraub; M. Marsel Mesulam; Eileen H. Bigio; Richard J. Miller; P. Hande Özdinler (Journal of Neuroinflammation, 2017)
Abstract Background Recent evidence indicates the importance of innate immunity and neuroinflammation with microgliosis in amyotrophic lateral sclerosis (ALS) pathology. The MCP1 (monocyte chemoattractant protein-1) and CCR2 (CC chemokine receptor 2) signaling system has been strongly associated with the innate immune responses observed in ALS patients, but the motor cortex has not been studied in detail. Methods After revealing the presence of MCP1 and CCR2 in the motor cortex of ALS patients, to elucidate, visualize, and define the timing, location and the extent of immune response in relation to upper motor neuron vulnerability and progressive degeneration in ALS, we developed MCP1-CCR2-hSOD1G93A mice, an ALS reporter line, in which cells expressing MCP1 and CCR2 are genetically labeled by monomeric red fluorescent protein-1 and enhanced green fluorescent protein, respectively. Results In the motor cortex of MCP1-CCR2-hSOD1G93A mice, unlike in the spinal cord, there was an early increase in the numbers of MCP1+ cells, which displayed microglial morphology and selectively expressed microglia markers. Even though fewer CCR2+ cells were present throughout the motor cortex, they were mainly infiltrating monocytes. Interestingly, MCP1+ cells were found in close proximity to the apical dendrites and cell bodies of corticospinal motor neurons (CSMN), further implicating the importance of their cellular interaction to neuronal pathology. Similar findings were observed in the motor cortex of ALS patients, where MCP1+ microglia were especially in close proximity to the degenerating apical dendrites of Betz cells. Conclusions Our findings reveal that the intricate cellular interplay between immune cells and upper motor neurons observed in the motor cortex of ALS mice is indeed recapitulated in ALS patients. We generated and characterized a novel model system, to study the cellular and molecular basis of this close cellular interaction and how that relates to motor neuron vulnerability and progressive degeneration in ALS.